ŚREDNIOWIECZNE INSPIRACJE W POEZJI CYPRIANA NORWIDA - Halkiewicz-Sojak, Grażyna (Colloquia Litteraria, 2017)
The author begins with underscoring Norwid’s defence of the intellectual achievements of the Middle Ages in part XII of Rzecz o wolności słowa. It prompts her to speculate about the importance and trajectories of reflections on the Middle Ages in Norwid’s poetry in general. Subsequently, Halkiewicz-Sojak casts the topic against the background concerning the romantic fascination with the Medieval tradition and specifically Polish difficulties in adapting the European (northern) variation of that current. On the one hand, Norwid’s considerations upon Godfred’s attitudes in Tasso’s Jersusalem Delivered and Cervantes’s Don Quixote lead to the conclusion that a nineteenth-century poet can only repeat Cervantes’s character’s gestures; therefore, for the author the Medieval props will be the book and the candle rather than a continuation of chivalrous adventures. On the other hand, Norwid – especially in the early drama mystery plays – conjures up poetic worlds of the Slavic Middle Ages and focuses his attention on the Christian initiation of the Slavdom.